Paper 40: Improved Cartilage Healing with Microfracture Augmented with Fisetin & Bone Marrow Aspirate Concentrate in Acute Osteochondral Defect. Issue 7 (30th July 2022) - Gao, Xueqin; Hambright, Sealy; Whitney, Kaitlyn; Huard, Matthieu; Murata, Yoichi; Nolte, Philip; Stake, Ingrid; Huard, Charles; Ravuri, Sudheer; Philippon, Marc; Huard, Johnny; Fukase, Naomasa
Objectives: Microfracture (MFx) technique is the most commonly used first-line treatment for cartilage injuries; however, it has been shown to have inferior long-term clinical outcomes as the repaired tissue is predominantly fibrocartilage. Bone Marrow Aspirate Concentrate (BMAC) treatment has been shown to enhance the healing ability of cartilage repair, superior to MFx treatment alone, although chondral defect filling was achieved with fibrocartilage or "hyaline-like" cartilage. Therefore, new therapeutic strategies to further improve cartilage healing following defects are in need. Fisetin (FIS) is a compound with antioxidant, anti-inflammatory, and senolytic activity capable of eliminating senescent cells systemically. Previous studies have reported that FIS attenuates the progression of osteoarthritis and osteoporosis in aged mice, however, whether FIS treatment improves the quality of repaired cartilage in MFx-treated acute osteochondral defects augmented with BMAC has not yet been investigated. We hypothesized that FIS or autologous BMAC, or a combination of the two, would enhance MFx procedure both histologically and mechanically in the repair of osteochondral defects in a rabbit model. Methods: All surgical procedures were performed by an experienced orthopaedic surgeon and followed Institutional IACUC approved protocols. Sixty-four skeletally mature New Zealand White rabbits at seven months old were used in this study.Animal procedure: Before surgery, bone marrow aspirate was collected through the iliac crests in each rabbit under anesthesia and processed via a two-step centrifugation method to prepare BMAC. After exposing the bilateral knee joints through the medial parapatellar approach, osteochondral defects (diameter: 5 mm, depth: 2 mm) were created bilaterally in the patellar groove of each rabbit, followed by the MFx procedure (5 holes with 2 mm depth) to allow bleeding at each MFx hole as previously described(Fig.1 ). BMACs were injected into the left knee joint as an autograft immediately after closing the joint capsule in all rabbits, with the right knee as a control (no BMAC transplantation). Rabbits were then randomly divided into 4 groups (N=8/group): MFx alone, MFx+FIS, MFx+BMAC and MFx+FIS+BMAC. FIS-treated rabbits were given FIS orally via drinking water at a dose of 20 mg/kg/day daily from immediately after surgery until euthanasia. Rabbits were sacrificed at 6 and 12 weeks post-op. The macroscopic appearance was evaluated using the International Cartilage Repair Society (ICRS) macroscopic assessment grading.ΜicroCT and histology: Microcomputed tomography (μCT) was performed to evaluate subchondral bone healing. Cartilage healing was assessed histologically on de-calcified tissue at 6 and 12 weeks post-op (H&E, Safranin O, and Alcian blue) and with immunohistochemistry for collagen II and p16. Regenerated cartilage was scored using the Modified O'Driscoll ICRS grading system (max 27 points). Biomechanical tests: The strength of the regenerated cartilage was analyzed by measuring the instantaneous elastic modulus of the regenerated cartilage in each group of samples collected at 12 weeks. (N=6/group). Results: Macroscopic assessment and μCT : At both 6 and 12 weeks postoperatively, MFx+BMAC and MFx+FIS+BMAC groups scored significantly higher than MFx alone group in the ICRS macroscopic evaluation. ( p < 0.01, Fig. 2 A, D and Fig. 3 A, D ). At both 6- and 12-week time points after surgery, μCT showed favorable healing of the bone defect in MFx+FIS, MFx+BMAC, and MFx+FIS+BMAC groups compared to MFx alone group. (Fig. 2 B and Fig. 3 B ). Histology : At both 6- and 12- week time points, the Modified O'Driscoll score was significantly higher in the MFx+BMAC and MFx+FIS+BMAC groups than in the MFx alone group ( p <0.01), and at 12 weeks, the MFx+FIS group had a significantly higher score than the MFx alone group. ( p <0.05, Fig. 2E and Fig. 3E) . In addition, immunohistochemistry showed stronger staining of type II collagen (brown) in the MFx+FIS, MFx+BMAC, and MFx+FIS+BMAC groups than in the MFx alone group at both time points, with a stronger reduction in staining of the cellular senescence marker p16 (brown) in FIS-treated group compared to MFx alone or MFx+BMAC group. (Fig. 2C and Fig. 3C) . Biomechanical analysis: The instantaneous elastic modulus (cartilage's strength) was significantly increased in the MFx+FIS+BMAC group compared to MFx alone group. ( p < 0.05, Fig. 4) . Gene expression analyses : qPCR showed the expression level of SOD1 in synovium was significantly higher in the MFx+FIS group at 6 weeks ( p < 0.01) and in the MFx+FIS+BMAC group at 12 weeks ( p < 0.05) compared to the MFx alone group. Conclusions: Our results showed that BMAC treatment enhanced the healing of MFx-treated osteochondral defects, macroscopically, biomechanically, and histologically, compared to MFx alone. Furthermore, FIS treatment improved MFx-treated cartilage repair, and its combined use with BMAC led to significantly higher quality cartilage regeneration with stronger mechanical properties. Oxidative stress, which is one of the inducers of cell senescence, has been noted as the primary factor contributing to age-related changes in cartilage homeostasis, function, and response to injury. Given the increase in SOD1 expression commensurate with p16 reduction in the FIS-treated group (Figs 2-3 ), our results suggest that FIS may improve cartilage healing via reducing cellular senescence. These results support the clinical use of FIS combined with BMAC to enhance the effect of MFx in the repair of osteochondral defects and highlight cellular senescence as a novel therapeutic target for cartilage repair following injury. Figure 1: Acute osteochondral defect microfracture rabbit model Figure 2: Macroscopy, MicroCT, and Histological findings at 6 weeks postoperatively A: Macroscopic findings. B: Micro CT showed better subchondral bone healing in the MFx+FIS, MFx+BMAC, and MFx+FIS+BMAC group. C: In the MFx+BMAC and MFx+FIS+BMAC groups, the ICRS macroscopic score was significantly increased compared to the MFx alone group. (D) In the MFx+BMAC and MFx+FIS+BMAC groups, the Modified O'Driscoll score increased significantly compared to the MFx alone group (E), indicating primarily hyaline-like cartilage regeneration. In addition, strong staining of type II collagen was observed in the MFx+FIS+BMAC groups, and there was a strong decrease in p16 (cellular senescence marker) staining in the FIS-treated group. * p < .05, ** p < .01. Figure 3: Macroscopy, MicroCT, and Histological findings at 12 weeks postoperatively A: Macroscopic findings. B: Micro CT showed better subchondral bone healing in the MFx+FIS, MFx+BMAC, and MFx+FIS+BMAC group. C: In the MFx+BMAC and MFx+FIS+BMAC groups, the ICRS macroscopic score was significantly increased compared to the MFx alone group. (D) In the MFx+FIS, MFx+BMAC, and MFx+FIS+BMAC groups, the Modified O'Driscoll score increased significantly compared to the MFx alone group (E), indicating primarily hyaline-like cartilage regeneration. In addition, strong staining of type II collagen was observed in the MFx+FIS, MFx+BMAC, and MFx+FIS+BMAC groups, and there was a strong decrease in p16 (cellular senescence marker) staining in the FIS-treated group. * p < .05, * * p < .01. Figure 4: Biomechanical findings at 12 weeks postoperatively Instantaneous elastic modulus (cartilage's strength) measurements for each group are shown, with a significant increase in the MFx+FIS+BMAC group compared to MFx alone group. * * P < .05